STRATEGI PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCE DI SEKOLAH DASAR - Fitri Siti Sundari (Jurnal Pendidikan Dasar, 2022)
Learning must be able to accommodate the various potentials that exist in students. Therefore, teachers must be able to use multiple intelligence-based learning strategies. This study aims to describe various learning strategies based on multiple intelligences in elementary schools. The research method used is the literature review method. There are 31 articles reviewed. The article was obtained from search results through google schoolar. The articles analyzed are articles that contain the keywords of multiple intelligence-based learning strategies. The results of the study show that there are 14 (fourteen) multiple intelligence-based learning strategies that are most often used by teachers in elementary schools, namely discussion strategies, action research, classification, analogies, identification, sociodrama, characterizations, flashcards, visual images, puppets, applied learning, movie learning, learning environment, and service learning.